2004
DOI: 10.1523/jneurosci.2786-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirements for Semaphorin 3F and Slit-1 in Axonal Targeting, Fasciculation, and Segregation of Olfactory Sensory Neuron Projections

Abstract: The formation of precise stereotypic connections in sensory systems is critical for defining accurate internal representations of the external world; however, the molecular mechanisms underlying the formation of sensory maps are poorly understood. Here, we examine the roles of two structurally unrelated repulsive guidance cues, semaphorin 3F (Sema3F) and Slit-1, in olfactory sensory axon fasciculation, targeting, and segregation. Using sema3F Ϫ/Ϫ mice, we show that Sema3F is critical for vomeronasal sensory ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
105
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 40 publications
6
105
3
Order By: Relevance
“…The perinatal lethality of robo-2 Ϫ/Ϫ mice precluded us from evaluating the requirement for Robo-2 in the development of accurate NQO-1-expressing axonal projections in the adult olfactory glomerular map. We therefore selectively ablated expression of Robo-2 in neurons by generating robo-2 conditional null mice that express the Cre (bacterio phage P1 cyclization recombinase) recombinase under the control of the pan-neuronal synapsin-1 (syn-1) promoter (Hoesche et al, 1993(Hoesche et al, , 1995Cloutier et al, 2004;Lu et al, 2007). robo-2 C/C ; syn-1 Cre/ϩ mice survive until adulthood, and their OBs are fully innervated by NQO-1-and OCAM-expressing axons.…”
Section: F G I J L M O) and Anti-ocam (B C E F H I Kmentioning
confidence: 99%
See 2 more Smart Citations
“…The perinatal lethality of robo-2 Ϫ/Ϫ mice precluded us from evaluating the requirement for Robo-2 in the development of accurate NQO-1-expressing axonal projections in the adult olfactory glomerular map. We therefore selectively ablated expression of Robo-2 in neurons by generating robo-2 conditional null mice that express the Cre (bacterio phage P1 cyclization recombinase) recombinase under the control of the pan-neuronal synapsin-1 (syn-1) promoter (Hoesche et al, 1993(Hoesche et al, , 1995Cloutier et al, 2004;Lu et al, 2007). robo-2 C/C ; syn-1 Cre/ϩ mice survive until adulthood, and their OBs are fully innervated by NQO-1-and OCAM-expressing axons.…”
Section: F G I J L M O) and Anti-ocam (B C E F H I Kmentioning
confidence: 99%
“…Moreover, we demonstrated previously that the Slit and Robo families of axon guidance cues can promote zonal segregation of vomeronasal axons in the accessory olfactory system in mice (Cloutier et al, 2004). We therefore evaluated whether SlitRobo signaling controls zonal segregation of OSNs in the main olfactory bulb.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Concomitantly, members of the plexin-A subfamily are expressed in the olfactory system, with robust expression of plexin-A1 (Plxna1) in the VNO and vomeronasal nerves (VNNs) (Murakami et al, 2001). Loss of Sema3A results in guidance errors in subsets of olfactory axons (Schwarting et al, 2000;Taniguchi et al, 2003), whereas loss of Sema3F or Npn-2 functions results in defasciculation of the VNNs along the medial surface of the olfactory bulb (Cloutier et al, 2002(Cloutier et al, , 2004Walz et al, 2002). Moreover, it has been reported that Npn-2 Ϫ/Ϫ mice are often infertile (Giger et al, 2000;Walz et al, 2002), prompting us to investigate the role of Npn-2 in the development and migration of GnRH neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest to olfactory behavior is the implication that class 3 soluble semaphorins and their receptors play a role in axon guidance in the mouse olfactory system (Renzi et al 2000;Schwarting et al 2000;Walz et al 2002;Taniguchi et al 2003;Cloutier et al 2004). A null mutation in Sema3F resulted in defasciculation of the vomeronasal nerve and rerouting of axons from vomeronasal sensory neurons into the main olfactory bulb.…”
mentioning
confidence: 99%